The impact of urban design decisions on net zero energy solar buildings in Sweden - Jouri Kanters; Maria Wall (Urban, Planning and Transport Research, 2014)
Planning for future energy-efficient and energy-producing buildings requires specific knowledge during the design process. Many design decisions taken by urban planners –form, density, roof type and orientation – have a significant effect on the conditions of such buildings, although urban planners might not always be aware of the effect of their design. This study examines the effects of important design decisions on the solar energy potential of net zero energy solar buildings. Typical Swedish building blocks with varying form, density, roof type and orientation were used to simulate the annual solar irradiation and energy production, and to calculate the load match for heating and electricity under Swedish conditions. Results of this study show that the urban density is the most influential parameter on the solar potential of building blocks. Furthermore, flat roofs often returned the highest load match value, while the effect of orientation on the solar potential turned out not to be that straightforward. With the results of this study, urban planners can make better informed decisions, while it also provides a ground for the net zero energy solar buildings discussion by exposing the boundaries of such buildings in the urban environment.